2008
DOI: 10.1021/ma801630n
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermal and Photochemical Strategies for Thiol−Ene Click Polymer Functionalization

Abstract: A series of alkene-functional polymers were synthesized by controlled polymerization techniques in order to investigate and compare the efficiency and orthogonality of both photochemically and thermally initiated thiol-ene click coupling reactions. The copolymers were designed to have single or multiple alkene-functional groups along the backbone, and to evaluate the robustness of these procedures, functionalization reactions with a library of mercaptans were studied. In comparing the photoinitiated reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
346
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(355 citation statements)
references
References 58 publications
5
346
0
4
Order By: Relevance
“…46,47 These reactions were also utilized as environmentally friendly "click" coupling processes in various synthetic applications, since in contrast to the other methods, they usually proceed in the absence of solvent under benign reaction conditions without the use of any potentially toxic metal. [48][49][50][51] For many curing applications fully formulated mixtures, which contain all initiators monomers and additives, are supplied to customers. However, such formulations may not exhibit a good shelf life due to the initiation on storage.…”
Section: Free Radical Systemsmentioning
confidence: 99%
“…46,47 These reactions were also utilized as environmentally friendly "click" coupling processes in various synthetic applications, since in contrast to the other methods, they usually proceed in the absence of solvent under benign reaction conditions without the use of any potentially toxic metal. [48][49][50][51] For many curing applications fully formulated mixtures, which contain all initiators monomers and additives, are supplied to customers. However, such formulations may not exhibit a good shelf life due to the initiation on storage.…”
Section: Free Radical Systemsmentioning
confidence: 99%
“…St [184] MMA [88] 323 [185] 40 [186] S S O O St [186] St-b-MAH [186] St-b-MAH-b-NIPAM [186] 41* [187,188] S S (MMA) [64,187,189] BA [187] EHA [188] St [190] TBAM [191] DEAM [187] DMAM [187] NAM [191] NIPAM [187,189] BA/St [192] EHA-b-MA [188] TBAM-b-NAM [191] DMAM/NAS [193] NAM-b-TBAM [191] 42* S S Ph CN MMA [194] 376 [195] 376-b-MMA [195] BA [196] MMA [189] NIPAM [189] MMA-b-NIPAM [189] MMA/283 [197] MMA/284 [197] St/2VP [198] St/348 [199] THPA-b-St [200] THPA-b-St/373 [201] 44 [202] [200] 47 [203] …”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…Styrene derivatives subjected to RAFT polymerization 348 [100,199] O 349 [138] O N N N 350 [158,309] N VBTAC 351 [159] Cl Ϫ Nϩ 352 [459] HN O 353 [321] O F F F F 354 [313] O F F F F 355 [313] [244] VBTPC 359 [34] Cl Ϫ P ϩ 360 [244] 361 [250] O N O 362 [207] O O O 363 [134] O O O Fe 364 [102] N 365 [102] N Table 23. Vinyl derivatives subjected to RAFT polymerization 366 [380] N 367 [380] N 368 [380] N 369 [390] N O O G. Moad, E. Rizzardo, and S. H. Thang [111,135] 370 [135,146] 375 [136] 376 [195] 377 [150] 378 [410] O O (H 3 C) 3 Si 372 [338,346,347] 373 [201] 374 [459] O [466] NAS 380 [160,299,317,345,347] 381 [178] 382 [222] [149,…”
Section: End-functional Polymers and End-group Transformationsmentioning
confidence: 99%
“…The UV-initiated thiol-ene click reaction was performed according to the method described by Campos et al (Campos et al 2008). In a vial, the prepared PHA bearing vinyl groups (PHAund60), thiol (10 eq with respect to the vinyl group), and DMPA (0.2 eq) were dissolved in either chlorobenzene or acetone.…”
Section: General Procedures For the Uv-initiated Thiol-ene Click Reactionmentioning
confidence: 99%
“…In addition to the CuAAc, the thiol-ene reaction is also important in the realm of click chemistry (Carioscia et al 2007;Hoyle andBowman 2010, Hoyle et al 2004;Li et al 2007). Campos et al reported the synthesis of various macromolecules via the UV-initiated thiol-ene click reaction, which proceeded quantitatively, with a high degree of specificity in a matter of minutes (Campos et al 2008;Killops et al 2008). However, the majority of PHAs studied to date contain no functional groups, and few groups have reported such modification of PHAs (Constantin et al 1999;Gagnon et al 1994a, b;Park, Lenz and Goodwin 1998).…”
Section: Introductionmentioning
confidence: 99%